Internal Student Mobility Among Universities in Kazakhstan: SWOT-Analysis (Journal of Educational Sciences, 2020)
Internal academic mobility is practiced between universities in Kazakhstan, and it is also one of the designated tasks of the State Program for the Development of Education and Science of the Republic of Kazakhstan for 2020-2025. Despite this, not enough attention is paid to the study of academic mobility is- sues both at the level of educational policy development and at the expert level, especially to the aspects of the development of internal academic mobility. Therefore, the purpose of this article is to conduct a SWOT analysis of the implementation of academic mobility programs based on the practices of universities and the experience of students who directly took part in the processes of internal academic mobility in Kazakh- stan to improve the effectiveness of these programs. The study used the case study method. The successful organization of internal mobility can become one of the factors for the development and creation of a more flexible, high-quality and competitive academic environment in Kazakhstan. In general, students of the regional university positively assessed the experience of short-term mobility in Kazakhstan. The results of the research can be used by employees and decision-makers in the field of higher education to build and develop mechanisms for the implementation of processes of internal academic mobility.Key words: higher education, case studies, academic mobility, internal academic mobility, SWOT- analysis.